THE FORMATION OF "TEEN FICTION" AND "YOUNG ADULT LITERATURE" IN WESTERN LITERATURE - Kasimova Yulduz Malikovna; Mamadaliyeva Sarvinoz Azamat qizi (The Conference Hub, 2025)
This article explores the historical development and cultural significance of "teen fiction" and "young adult (YA) literature" within the context of Western literary traditions. Tracing its roots from early 20th-century coming-of-age narratives to the rise of a distinct YA market in the post-World War II era, the study examines how shifting societal attitudes toward adolescence influenced literary production.
Keywords: Young adult literature, teen fiction, adolescence in literature, Western literary history, coming-of-age, youth culture, literary genres, identity, cultural studies, Bildungsroman, publishing trends.